Red-crested cardinal defences against shiny cowbird parasitism - Segura, Luciano Noel (2012)
Avian brood parasites reduce the reproductive success of the host, which favours the evolution of antiparasitic defences, such as aggression towards parasites or rejection of their eggs. The red-crested cardinal, Paroaria coronata, is a potential good-quality host of the shiny cowbird, Molothrus bonariensis. However, the frequency of cowbird parasitism in cardinal nests is very low and there are no records of this host raising parasite's chicks, which suggest that it may have evolved effective antiparasitic defences. We studied cardinal antiparasitic defences by: (1) presenting dummy models of a female cowbird and non-predator and predator control species to nests during laying and incubation, and (2) conducting experiments of artificial parasitism with natural cowbird eggs of different morphs and conspecific eggs during laying and early and late incubation. We found that: (1) the frequency of cowbird parasitism in cardinal nests was 7%, (2) cardinals did not exhibit aggressive behaviours towards cowbird or nonpredator models but responded aggressively towards a predator model, (3) they rejected parasite eggs in 98.5% of the cases (mostly through egg ejection), but conspecific eggs in only 6% of the cases, (4) there were no costs (breakage or ejection of their own eggs) associated with ejection of the parasite's eggs, and (5) a relatively low frequency of parasitism is enough selection pressure to maintain egg rejection at a high level. The antagonistic expression of antiparasitic defences in red-crested cardinals suggests that they may have lost the behaviour of aggression towards the parasite as a result of associated costs.